EDUKASI CERDIK TERHADAP PENINGKATAN PENGETAHUAN PENCEGAHAN DIABETES DAN HIPERTENSI PADA LANSIA PROLANIS PUSKESMAS GEDEG KABUPATEN MOJOKERTO - Rayhan Saiful Rahman; Nyoman Sri Devi Mahotami; Ni Putu Chintya Eka Shanty; Jesuina Istinah Matos; Nyoman Nugraha Wirajaya; Shifa Alvin Aushafira; Muhibbatul Lubaba; Mohammad Syafiki Al Maulidi; Wike Herawaty (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Diabetes mellitus and hypertension are non-communicable diseases with a high prevalence among the elderly and are major causes of morbidity and mortality. Low levels of awareness and adherence to a healthy lifestyle further exacerbate these conditions. The CERDIK Elderly Program (Preventing Diabetes and Hypertension through a Healthy Lifestyle) is a simple and effective educational approach to increase elderly awareness regarding chronic disease prevention. Objective: To determine the improvement in PROLANIS participants’ knowledge regarding the prevention of diabetes and hypertension through CERDIK education. Methods: The educational activity was conducted on November 14, 2025, using leaflet media. Knowledge assessment was carried out using a questionnaire consisting of 10 questions administered before and after the counseling session to 50 elderly participants. Results: The average pre-test score of 72 increased to 89 in the post-test, indicating a 23.6% improvement in knowledge. Participants showed high enthusiasm during the educational session. Conclusion: CERDIK education was proven effective in increasing knowledge related to the prevention of diabetes and hypertension among the elderly group.